Orthotitanate microwave ceramic material with high temperature stability and preparation method thereof

By adding metal ions such as Zn, Li, Co, Ni to the microwave ceramic material and optimizing the sintering temperature, the problem of large τf value of existing ceramic materials is solved, high temperature stability and excellent dielectric performance are achieved, and it is suitable for the new generation of wireless mobile communication and microwave communication.

CN119569444AActive Publication Date: 2025-03-07CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411856955.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The resonant frequency temperature coefficient (τf) of existing microwave ceramic materials is large, which limits its application in microwave communication systems and is costly and difficult to widely use in engineering production.

Method used

By adding low-cost metal ions such as Zn, Li, Co, Ni, etc., the chemical composition of the ceramic is adjusted to [(Mg1/2Zn1/2)0.4+xLi0.4(Co1/2Ni1/2)0.4-x]2TiO4, the resonance frequency temperature coefficient is optimized, and the material performance is further optimized by controlling the sintering temperature.

Benefits of technology

The high temperature stability of the ceramic is achieved, the resonance frequency temperature coefficient is close to zero, the dielectric constant is between 15 and 17, and the Qf value can reach 106,000 GHz, which is low in cost, simple in preparation process, and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569444A_ABST
    Figure CN119569444A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-stability orthotitanate microwave ceramic material and a preparation method thereof, and belongs to the field of microwave electronic ceramic materials and preparation thereof, the chemical composition of the material is [(Mg1 / 2Zn1 / 2) 0.4 + xLi0.4 (Co1 / 2Ni1 / 2) 0.4-x] 2TiO4, 0 < = x < = 0.4, the preparation method comprises the steps of primary ball milling, pre-sintering, secondary ball milling, granulation, high-temperature sintering and the like, the sintering temperature is 1300-1400 DEG C, and the sintering time is 2-4 hours; the temperature coefficient of resonance frequency of the material can reach-27 ppm / DEG C, the dielectric constant ranges from 15 to 17, the Qf value can reach 106000 GHz, and the material has wide application prospects in new-generation wireless mobile communication and microwave communication. And the preparation method is low in cost, simple in preparation process, easy to operate and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave electronic ceramic materials and preparation thereof, in particular to an orthotitanate microwave ceramic material with high temperature stability and a preparation method thereof. Background Art

[0002] With the innovation of the new generation of wireless communication network technology, the environment in which electronic components are used has become more complex, which has put forward higher requirements on the stability of microwave components. f ), as an important indicator of the temperature stability of microwave dielectric ceramics, the closer its absolute value is to 0, the better the temperature stability of the ceramics. Therefore, the demand for microwave dielectric ceramics with a resonant frequency temperature coefficient approaching zero in the field of communication equipment is becoming increasingly urgent.

[0003] In order to improve the temperature stability of ceramics, many scholars have f The material is used as a resonant frequency temperature coefficient compensator. Two-phase composites are common to improve ceramic τ with temperature coefficient compensation. f Method, τ of 0.94Mg2TiO4-0.06SrTiO3 composite ceramics f The value is -3.3 ppm / ℃, but the Qf value is 70 900 GHz, and the different crystal structures of Mg2TiO4 and SrTiO3 cause them to coexist as different phases, which may cause changes in the dielectric properties of the composite materials.

[0004] Ion substitution is a common method to improve the performance of microwave dielectric ceramics, but most ion substitutions optimize the quality factor of ceramics. Xu et al. used ion substitution to improve the performance of microwave dielectric ceramics. 2+ Substitute Ca in A position 2+ and use W 6+ Substitute Nb in B position 5+ , optimizes the resonant frequency temperature coefficient. (Ce 0.85 Ca 0.15 )(Nb 0.85 W 0.15 )O4ε r = 19.7, Qf = 35,450 GHz, τ f = 0.8 ppm / °C. However, due to the scarcity and high price of Ce and Nb metals, it is difficult to widely use them in engineering production.

[0005] Titanates have attracted extensive attention due to their superior properties. As a member of the titanate system, Mg2TiO4 has good dielectric properties: ε r=14.51, Qf = 161 570 GHz, microwave dielectric ceramic devices made of Mg2TiO4 can reduce the dielectric loss of microwave devices, but they have a poor resonant frequency temperature coefficient (τ f = -50 ppm / ℃), which limits its widespread application in microwave communication systems. Summary of the invention

[0006] One of the purposes of the present invention is to provide a high temperature stability orthotitanate microwave ceramic material to solve the above problems.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a high temperature stability orthotitanate microwave ceramic material, the chemical composition of the material is: [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO 4, Among them, 0≤x≤0.4.

[0008] τ for Mg2TiO4 microwave ceramics f The inventors proposed a method that is low in cost, simple in preparation process, easy to operate and can significantly optimize τ f The material is mainly achieved by adding low-cost metal ions such as Zn, Li, Co, and Ni, and adjusting τ through multi-ion coupling. f Optimization.

[0009] As a preferred technical solution, 0.1≤x≤0.3, within this range, the resonant frequency temperature coefficient of the material is closer.

[0010] The above-mentioned microwave dielectric ceramics further control the sintering temperature at 1300-1400 °C, and the resonant frequency temperature coefficient can reach -27 ppm / °C when x=0.2, the dielectric constant is between 15 and 17, and the Qf value can reach 106000 GHz; it has broad application prospects in the new generation of wireless mobile communications and microwave communications.

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned orthotitanate microwave ceramic material with high temperature stability, comprising the following steps:

[0012] (1) MgO, ZnO, CoCO3, NiCO3, Li2CO3 and TiO2 are used as raw materials, and the raw materials are weighed according to the original proportions of the chemical composition, and then ball milled and dried to obtain dried materials;

[0013] (2) pre-burning the dried material obtained in step (1) to obtain a pre-burned material;

[0014] (3) placing the pre-sintered material obtained in step (2) into a ball mill and performing secondary ball milling to obtain a slurry;

[0015] (4) drying the slurry obtained in step (3) to constant weight, granulating the slurry, and pressing the slurry into samples;

[0016] (5) placing the sample obtained in step (4) in a high-temperature sintering furnace, heating the temperature to 400-600°C at a heating rate of 3-6°C / min and keeping the temperature for 2-6 h, and finally cooling the sample to room temperature in the furnace to obtain a debinding green sample;

[0017] (6) The green sample obtained in step (5) is placed in a high-temperature sintering furnace, and the temperature is raised to 1300-1400°C at a heating rate of 3-6°C / min, and kept at this temperature for 2-6 hours. Finally, the green sample is cooled to room temperature in the furnace to obtain a titanate microwave dielectric material with an optimized resonant frequency temperature coefficient.

[0018] As a preferred technical solution, in both step (1) and step (3), zirconium oxide balls are used as grinding balls and deionized water is used as the ball milling medium.

[0019] As a preferred technical solution, in step (2), the pre-sintering method is: placing the dried material into an alumina crucible and compacting it, heating the raw material to 1100°C at a heating rate of 3-6°C / min, then keeping the material warm for 2-6 hours, and then cooling it to room temperature with the furnace.

[0020] As a preferred technical solution, in step (4), 10 wt % PVA solution is added as a binder during granulation.

[0021] As a preferred technical solution, in step (4), the pressure during tableting is 20 MPa, and the size of the pressed cylindrical sample is: diameter 12 mm × thickness 4~6 mm

[0022] As a preferred technical solution, in step (6), the sintering temperature is 1400°C. Sintering at this temperature has better material properties. f The value can reach -28.7 ppm / ℃, ε r = 16.113, Qf = 106 0000 GHz.

[0023] Compared with the prior art, the advantages of the present invention are: the material of the present invention regulates the resonant frequency temperature coefficient of the ceramic through multi-element coupling to reach -27 ppm / ℃, the dielectric constant is between 15 and 17, and the Qf value can reach 106000 GHz (without significant deterioration), and has broad application prospects in the new generation of wireless mobile communications and microwave communications; and the material of the present invention has low cost, simple preparation process, easy operation, and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an X-ray diffraction (XRD) pattern of the sample with x = 0.0-0.4 sintered at 1400° C. in Example 1 of the present invention;

[0026] Figure 2 For Example 1 of the present invention [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO4 dielectric properties of samples with x=0.0~0.4 sintered at 1400 ℃;

[0027] Figure 3 For Example 2 [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO4 dielectric properties of samples with x = 0 sintered at 1300 ℃ ~ 1400 ℃.

[0028] Figure 4 For Example 3 (Mg 0.25 Zn 0.2 Co 0.25 Ni 0.25 )2TiO4 dielectric properties of samples sintered at 1300 ℃ and 1350 ℃. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with embodiments.

[0031] A high temperature stability orthotitanate microwave ceramic material, the preparation method of which comprises the following steps:

[0032] Step 1: Follow [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO4 where x=0.0~0.4 is used to weigh and prepare the raw materials; the prepared raw materials are placed in a ball mill filled with zirconium balls, deionized water is used as the ball milling medium, the ball mill speed is set to 250 rpm, the ball milling time is set to 4 h, and after the ball milling is completed, the slurry is placed in a constant temperature drying oven and dried to constant weight for standby use;

[0033] Step 2: The agglomerated powders after drying in step 1 are crushed in a mortar, put into a crucible for compaction, and first heated to 100 °C at a heating rate of 5 °C / min, and then heated to 1100 °C at a heating rate of 10 °C / min for pre-sintering; then the material is kept warm for 4 h, and then cooled to 500 °C at a rate of 5 °C / min and then cooled to room temperature with the furnace to obtain the pre-sintered material, which is put into a ball mill for secondary ball milling and mixing;

[0034] Step 3: Add 10 wt% PVA solution as a binder to the powder obtained in step 2, granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;

[0035] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4 h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;

[0036] Step 5: Place the green sample after debinding in step 4 into the high-temperature sintering furnace again, and heat it to 100 °C at a heating rate of 5 °C / min, then to 1000 °C at a heating rate of 10 °C / min, and then to 1400 °C at a heating rate of 5 °C / min for sintering, and keep it at that temperature for 4 h. After the heat preservation, reduce the temperature to 500 °C at a heating rate of 5 °C / min and cool it to room temperature with the furnace to obtain τ f Significantly improve titanate microwave dielectric materials;

[0037] Figure 1 The XRD patterns of the samples sintered at 1400°C for the materials with different x values ​​in this embodiment are shown in Figure 2. Figure 1 It can be seen that the samples are M2TiO4 (M is Mg, Zn, Co, Ni and Li) phase and NiO phase.

[0038] Different x values ​​[(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni1 / 2 ) 0.4-x ]2The microwave dielectric properties of TiO4 are as follows Figure 2 shown; from Figure 2 As can be seen from the figure, as x increases, τ f First increase and then decrease, τ f = -27~-44ppm / ℃, when x = 0.3, τ f = -28.7 ppm / ℃, Qf = 106 000 GHz, ε r = 16.13, and when x = 0.2, τ f = -27 ppm / °C.

[0039] Embodiment 2:

[0040] A high temperature stability orthotitanate microwave ceramic material, the preparation method of which comprises the following steps:

[0041] Step 1: Follow [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO4 ratio to weigh and prepare the raw materials; place the prepared raw materials in a ball mill filled with zirconium balls, use deionized water as the ball milling medium, set the ball mill speed to 250 rpm, and set the ball milling time to 4 h. After the ball milling, place the slurry in a constant temperature drying oven and dry it to constant weight for use.

[0042] Step 2: The agglomerated powders after drying in step 1 are crushed in a mortar, put into a crucible for compaction, and first heated to 100 °C at a heating rate of 5 °C / min, and then heated to 1100 °C at a heating rate of 10 °C / min for pre-sintering; then the material is kept warm for 4 h, and then cooled to 500 °C at a rate of 5 °C / min and then cooled to room temperature with the furnace to obtain the pre-sintered material, which is put into a ball mill for secondary ball milling and mixing;

[0043] Step 3: Add 10 wt% PVA solution as a binder to the powder obtained in step 2, granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;

[0044] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4 h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;

[0045] Step 5: Put the green sample after debinding in step 4 into the high-temperature sintering furnace again, and heat it to 100 °C at a heating rate of 5 °C / min, and then heat it to 1000 °C at a heating rate of 10 °C / min. Sinter one of them at 1300 °C, and heat the other two to 1350 °C and 1400 °C at 5 °C / min, respectively, and keep them warm for 4 h. After the heat preservation, reduce the temperature to 500 °C at 5 °C / min and cool it to room temperature with the furnace to obtain τ f Improving titanate microwave dielectric materials.

[0046] [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO4(x = 0.3)Microwave dielectric properties are as follows Figure 3 As shown. Figure 3 It can be seen that when the sintering temperature is 1300 ℃ ~ 1400 ℃, τ f Between -40 ppm / ℃ and -27 ppm / ℃, Qf between 2500 GHz and 106000 GHz, ε r Between 16.13 and 17.02, when the sintering temperature is 1400 °C, τ f = -28.7 ppm / ℃, Qf = 106 000 GHz, ε r = 16.13.

[0047] Embodiment 3:

[0048] A high temperature stability orthotitanate microwave ceramic material, the preparation method of which comprises the following steps:

[0049] Step 1: Follow (Mg 0.25 Zn 0.2 Co 0.25 Ni 0.25 )2TiO4 in a certain proportion to weigh and prepare the raw materials; place the prepared raw materials in a ball mill filled with zirconium balls, use deionized water as the ball milling medium, set the ball mill speed to 250rpm, and set the ball milling time to 4 h. After the ball milling, place the slurry in a constant temperature drying oven and dry it to constant weight for use.

[0050] Step 2: The agglomerated powders after drying in step 1 are crushed in a mortar, put into a crucible for compaction, and first heated to 100 °C at a heating rate of 5 °C / min, and then heated to 1100 °C at a heating rate of 10 °C / min for pre-sintering; then the material is kept warm for 4 h, and then cooled to 500 °C at a rate of 5 °C / min and then cooled to room temperature with the furnace to obtain the pre-sintered material, which is put into a ball mill for secondary ball milling and mixing;

[0051] Step 3: Add 10 wt% PVA solution as a binder to the powder obtained in step 2, granulate, and uniaxially dry press into a cylinder of 12 mm (diameter) × 6 mm (thickness) at 20 MPa;

[0052] Step 4: Place the green sample obtained in step 3 into a high-temperature sintering furnace, heat it to 100°C at a heating rate of 5°C / min, then heat it to 600°C at a heating rate of 10°C / min and keep it at that temperature for 4 h, finally cool it to 500°C at a heating rate of 5°C / min and then cool it to room temperature with the furnace to obtain a green sample after debinding;

[0053] Step 5: Place the green sample after debinding in step 4 back into the high-temperature sintering furnace, and heat it to 100 °C at a heating rate of 5 °C / min, and then heat it to 1000 °C at a heating rate of 10 °C / min. Sinter the two pieces at 1300 °C and 1350 °C at 5 °C / min, respectively, and keep them warm for 4 h. After the heat preservation, reduce the temperature to 500 °C at 5 °C / min and cool to room temperature with the furnace to obtain titanate microwave dielectric material.

[0054] (Mg 0.25 Zn 0.2 Co 0.25 Ni 0.25 )2The microwave dielectric properties of TiO4 are as follows Figure 4 As shown. Figure 4 It can be seen that when the sintering temperature is 1300 ℃, τ f is -46 ppm / ℃, Qf is 50800 GH, ε r is 16.6. When the sintering temperature is 1350℃, τ f is -41 ppm / ℃, Qf is 45800 GH, ε r It is 17.1.

[0055] It can also be seen from this embodiment that the addition of Li ions plays an important role in improving the performance of the material.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature stability orthotitanate microwave ceramic material, characterized in that: The chemical composition of the material is: [(Mg 1 / 2 Zn 1 / 2 ) 0.4+x Li 0.4 (Co 1 / 2 Ni 1 / 2 ) 0.4-x ]2TiO 4, Among them, 0≤x≤0.

4.

2. The orthotitanate microwave ceramic material with high temperature stability according to claim 1, characterized in that: 0.1≤x≤0.3。 3. The method for preparing the orthotitanate microwave ceramic material with high temperature stability according to claim 1 or 2, characterized in that: The steps include: (1) MgO, ZnO, CoCO3, NiCO3, Li2CO3 and TiO2 are used as raw materials, and the raw materials are weighed according to the original proportions of the chemical composition, and then ball milled and dried to obtain dried materials; (2) pre-burning the dried material obtained in step (1) to obtain a pre-burned material; (3) placing the pre-sintered material obtained in step (2) into a ball mill and performing secondary ball milling to obtain a slurry; (4) drying the slurry obtained in step (3) to constant weight, granulating the slurry, and pressing the slurry into samples; (5) placing the sample obtained in step (4) in a high-temperature sintering furnace, heating the temperature to 400-600°C at a heating rate of 3-6°C / min and keeping the temperature for 2-6 h, and finally cooling the sample to room temperature in the furnace to obtain a debinding green sample; (6) The green sample obtained in step (5) is placed in a high-temperature sintering furnace, and the temperature is raised to 1300-1400°C at a heating rate of 3-6°C / min, and kept at this temperature for 2-6 hours. Finally, the green sample is cooled to room temperature in the furnace to obtain a titanate microwave dielectric material with an optimized resonant frequency temperature coefficient.

4. The method according to claim 3, characterized in that: In both step (1) and step (3), zirconium oxide balls are used as grinding balls and deionized water is used as ball milling medium.

5. The method according to claim 3, characterized in that: In step (2), the pre-sintering method is: placing the dried material into an alumina crucible and compacting it, heating the raw material to 1100°C at a heating rate of 3-6°C / min, then keeping the material warm for 2-6 hours, and then cooling it to room temperature with the furnace.

6. The method according to claim 3, characterized in that In step (4), 10 wt % PVA solution is added as a binder during granulation.

7. The method according to claim 3, characterized in that In step (4), the pressure during tableting is 20 MPa, and the dimensions of the pressed cylindrical sample are: diameter 12 mm × thickness 4~6 mm.

8. The method according to claim 3, characterized in that In step (6), the sintering temperature is 1400°C.

Citation Information

Patent Citations

  • Method of manufacturing sintered body containing spinel type lithium titanate

    JP2019077573A